Long-Term Clinical Outcomes After Procedural Hemopericardium Requiring Pericardiocentesis During Atrial Fibrillation Ablation - Soohyun Kim; Soyoon Park; Hwajung Kim; Young Choi; Yong-Seog Oh; Sung-Hwan Kim (Journal of Cardiovascular Development and Disease, 2026)
Hemopericardium is a rare but serious complication of radiofrequency catheter ablation (RFCA) for atrial fibrillation (AF). While prompt pericardial drainage is effective, the long-term clinical course and the role of adjunctive anti-inflammatory therapy remain unclear. In this prospective single-center cohort study, we included patients who developed hemopericardium requiring pericardiocentesis during RFCA for AF. All patients underwent immediate percutaneous drainage. Colchicine (0.6 mg twice daily for 14 days) was prescribed at the operator’s discretion. The primary outcome was freedom from AF or atrial tachycardia (AT) at 12 months after a 3-month blanking period. Among 2133 patients undergoing RFCA, 75 (3.5%) developed hemopericardium. Of these, 21 received colchicine and 54 received usual care. During a median follow-up of 367 days, freedom from AF/AT did not differ between groups (76.2% vs. 74.1%, log-rank p = 0.93). Residual pericardial effusion was infrequent and resolved in all patients by 3 months. Although colchicine was not associated with a reduction in atrial arrhythmia recurrence, patients receiving colchicine had lower CRP levels at 3 months than those receiving usual care (p = 0.021). However, treatment-limiting adverse events occurred in 6 of 21 patients (28.6%) receiving colchicine. No cases of constrictive pericarditis were observed. In patients with procedural hemopericardium during AF ablation, prompt pericardial drainage was associated with favorable clinical outcomes and absence of long-term pericardial sequelae. Adjunctive colchicine therapy was not associated with a significant reduction in arrhythmia recurrence; however, given the small sample size and limited number of events, a clinically meaningful treatment effect cannot be excluded.